CHOICE OF BLENDED LEARNING MODELS FOR HIGHER PEDAGOGICAL EDUCATION STUDENTS - Т. Собченко (Фізико-математична освіта)
Problem formulation. The development of information and computer technologies is quite rapid. The realities of today are that higher education institutions must introduce new and effective teaching methods and technologies that will help to improve the quality of education. The large-scale introduction of online technologies, various models of blended learning is relevant, which leads to fundamental changes in approaches to the organization of education in higher education institutions and in each discipline, especially the role of the audience classes and its effectiveness.